Validation of an endoscopic flavectomy training model - KULCHESKI,ÁLYNSON LAROCCA (2021)
ABSTRACT Objective: to validate a lumbar spine endoscopic flavectomy simulator using the construct method and to assess the acceptability of the simulator in medical education. Methods: thirty medical students and ten video-assisted surgery experienced orthopedists performed an endoscopic flavectomy procedure in the simulator. Time, look-downs, lost instruments, respect for the stipulated edge of the ligamentum flavum, regularity of the incision, GOALS checklist (Global Operative Assessment of Laparoscopic Skills), and responses to the Likert Scale adapted for this study were analyzed. Results: all variables differed between groups. Procedure time was shorter in the physician group (p < 0.001). Look-downs and instrument losses were seven times greater among students than physicians. Half of the students respected the designated incision limits, compared to 80% of the physicians. In the student group, about 30% of the incisions were regular, compared to 100% in the physician group (p < 0.001). The physicians performed better in all GOALS checklist domains. All the physicians and more than 96% of the students considered the activity enjoyable, and approximately 90% believed that the model was realistic and could contribute to medical education. Conclusions: the simulator could differentiate the groups’ experience level, indicating construct validity, and both groups reported high acceptability.